1975
DOI: 10.1002/pssb.2220720244
|View full text |Cite
|
Sign up to set email alerts
|

On exciton absorption, band structure, and phase transformation of GaSe under pressure

Abstract: The spectra of the absorption coefficient (a) of GaSe a t the photon energy range 1.94 t o 2.64 eV and a t pressures between 1 bar and 12 kbar are investigated a t 295 O K . Data a t 1 t o 4360 bar confirm that the edge exciton of GaSe is the direct allowed one. The pressure coefficient of the band gap (dE,/dP = -6.2 x eV bar-I), one of the Rydberg exciton constant (dR/dP = -0.6 x eV bar-*), and one of the exciton effective massIt is supposed that two interband exciton transitions a t 2.001 and 3.25 eV give th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…-As is well known, gallium sulphide, selenide and telluride are semiconducting layer structure compounds built up from weakly interacting two-dimensional layers. A lot of theoretical and experimental information [1][2][3][4][5][6][7][8][9][10][11][12][13] is available on these III-VI semiconductors. Recent thermoreflectance [14,15], electroreflectance [16][17][18] and wavelength modulation [19] together with normal reflectivity [20] and absorption [21] measurements have been carried Qut, making an interpretation of the main optical behaviour of these compounds possible.…”
mentioning
confidence: 99%
“…-As is well known, gallium sulphide, selenide and telluride are semiconducting layer structure compounds built up from weakly interacting two-dimensional layers. A lot of theoretical and experimental information [1][2][3][4][5][6][7][8][9][10][11][12][13] is available on these III-VI semiconductors. Recent thermoreflectance [14,15], electroreflectance [16][17][18] and wavelength modulation [19] together with normal reflectivity [20] and absorption [21] measurements have been carried Qut, making an interpretation of the main optical behaviour of these compounds possible.…”
mentioning
confidence: 99%
“…These authors reported complex behavior including (i) a nonlinear pressure dependence of the direct bangap, exhibiting a low-pressure interval with negative pressure coefficient and then increasing with pressure after a minimum, as shown in Figure 5b; (ii) a large negative pressure coefficient for the indirect gap of GaS; and (iii) a progressive widening and disappearing of the exciton peak, as shown in Figure 5a. Concerning ε-GaSe, Panfilov et al [50] suggested that nonlinear behavior was the result of a phase transition to a different polytype occurring at 0.6 GPa, a hypothesis that was not supported by later XRD experiments [32,34]. badgap of 2 eV at RT [46].…”
Section: Optical Measurements and Ab-initio Band Structure Calculationsmentioning
confidence: 96%